Sense of Belonging and Self-esteem of High School Students in a Catholic College - Suan, MSLT, Maria Madelyn D.; Magallanes , Celo I. (Philippine Social Science Journal, 2020)
A sense of belonging in the cycle of teaching and learning is important to students because if they understand acceptance into the program, they will feel more inspired, more successful, and more driven. Students understand the value of school activities in a supportive and warm atmosphere that provides a sense of belonging and acceptance. Moreover, it is a vital necessity for every individual. The sense of belonging for schools is about achievement, suggesting that the benefit of fulfilling this need is generally higher, reaching the students. Therefore, students who do not fulfill their needs for possessions will also have lower self-esteem. Low self-esteem is often associated with depression. Low self-esteem can lead to depression, and depression lowers self-esteem. Hence, the paper describes the extent of belongingness and level of self-esteem of high school students of a Catholic college in Antique during the school year 2019-2020. Likewise, this paper explored the relationship between the students’ demographics and their sense of belongingness and self-esteem.